PELAKSANAAN HAḌANAH PASCA PERCERAIAN DI DESA SINDUADI, MLATI, SLEMAN, YOGYAKARTA: TINJAUAN HUKUM ISLAM DAN HUKUM POSITIF - Sholihah, Mar’atush (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
The background of this research is because parents underestimate and ignore their responsibilities. This is not in accordance with the provisions of Islamic law and positive law in Indonesia, causing children's rights to not be fulfilled for various reasons. Seeing these conditions, a sustainable concrete solution is needed to deal with this situation. This paper is prescriptive and uses a normative juridical approach. To see the role and function of writing, the theory of Maqāṣid Syarī'ah Abū Ishāq as-Syatibī is used, where the writing of the implementation of haḍanah is in the realm of arrūiyyāt. The results of this study indicate that: the implementation of post-divorce haḍanah in Sinduadi Village by parents of children who have not been mumayiz raised by the mother, so that the mother becomes a single parent. In addition to caring for children, mothers also have to work to meet their daily needs, so that care is taken over by the mother (grandmother) or close relatives when they leave work. Judging from the obligations of ex-husbands in fulfilling children's rights, all of them have not been fulfilled and carried out according to the applicable normative and juridical principles. Several factors become obstacles, including economic limitations, already having a new family and the low level of parental care, especially ex-husbands for their children. Parenting must be done with full attention and affection, this aims to create a good generation. Judging from the aspects of education and upbringing which in this case fall to the wife, the wives have understood and continue to do their best for their children in order to create a generation that is superior and has noble character.